Visual capture of apparent limb position influences tactile temporal order judgments. - Gallace, A; Spence, C (2005)
Shore et al. [D.I. Shore, E. Spry, C. Spence, Spatial modulation of tactile temporal order judgments, Perception (submitted for publication)] recently demonstrated that people find it easier to judge which hand is touched first (in a tactile temporal order judgment task) when their hands are placed far apart rather than close together. In the present study, we used a mirror to manipulate the visually perceived distance between participants' hands, while holding the actual (i.e., proprioceptively-specified) distance between them constant. Participants were asked to determine which of two vibrotactile stimuli, one presented to either index finger using the method of constant stimuli, was presented first. Performance was significantly worse (i.e., the JND was larger) when the hands were perceived (due to the mirror reflection) as being close together rather than further apart. These results highlight the critical role that vision plays in influencing the conscious perception of the temporal order of tactile stimuli.